Effect of triphala on growth, immunity, related gene expression and intestinal morphometry of yellow perch (Perca flavescens). - Hiam Elabd; Wang, Han Ping; Rafidah Othman; HongYao (Public Library Science, 2025)
The current study evaluated the effects of dietary supplementation of Triphala (TR) on yellow perch (Perca flavescens) growth performance, immune response, related gene expression, and intestinal histological structure. The experimental design included four groups: one control group (0% TR/ kg diet) and three TR-supplemented groups with 2, 4, and 6%/kg diet for four weeks and each group was allocated in triplicates with 30 fish each. Sampling included three fish from each replicate for evaluating immune response and gene expression. Findings showed that Triphala markedly improved growth performance, Immunoglobulin M (IgM) levels, lysozyme activity, and Nitric Oxide (NO) activity with the most significant (p < 0.05) results for 6% TR/kg diet group. The TR groups also showed significantly decreased glucose and cortisol concentrations with the lowest values for the 6% TR/kg diet group. Moreover, TR-incorporated groups revealed significantly upregulated expression (p < 0.05) of growth [Insulin-Like Growth Factor-1 (IGF-1)] and immune [Alpha 2 Macroglobulin (A2M), Serum Amyloid A (SAA) and Complement Component C3 (CCC3)] genes in incorporated groups, specially the 6% TR group. Moreover, the intestinal morphometric histological analysis revealed that villus length was increased in a dose-dependent manner, coping with other enhanced parameters. Current results endorse the positive effects of Triphala incorporation on yellow perch farming as a safe alternative option to enhance growth performance, immune response, related gene expression, and intestinal histology.